Incidence of Industrial Employees Having Standard Threshold Shifts; A Study of the Existing Audiograms - Pimda, Pornthip; Chaiear, Naesinee; Yimtae, Kwanchanok; Khiewyoo, Jiraporn; Thanawiratananit, Panida; Krusun, Napaporn (Srinagarind Medical Journal, 2016)
Background and Objective: Prolonged occupational noise exposure can cause noise-induced hearing loss(NIHL) which is an irreversible disease. Standard threshold shift (STS) is the criteria recommended by OSHA for early detection of NIHL. There are limited studies on STS and hearing conservation programs in Thailand. The objective of this study is to estimate the incidence of the industrial workers who acquire STS. Methods: A retrospective descriptive was performed. The study populations were 224 workers who were audiometric examined by the in-house occupational health services at Khon Kaen University during the years 2009 to 2013. The study tools comprised of 1) the existing completed self –administered questionnaire and 2) the existing audiograms obtained from the previous audiometric examinations. Data was analyzed and reported as incidence and 95%CI. Results: Our studied sample included 274 workers who had at least two consecutive audiograms (588 audiograms). Two-hundred and twenty four workers (488 audiograms) were compatible with inclusion criteria. Most workers were in production processes (87.1%). Incidence of STS with age correction and without age correction were 5.4%(95% CI: 2.8, 9.2) and 6.3% (95%CI: 3.5, 10.3), respectively. Incidence of early NIHL was 13.4% (95%CI: 9.2, 18.6). Most subjects who had STS and early NIHL were found in manufacturer of cotton products. Conclusions: This study concluded that theof STS was 5.4%(95% CI: 2.8, 9.2). Aneffective hearing conservation program is strictly needed for industrial employees.